The secure child : timeless lessons in parenting and childhood education - Volpe, Richard (Emerald Publishing Limited : Information Age Publishing, 2010)
The Secure Child: Timeless Lessons In Parenting and Childhood Education was designed to contribute meaning to the adage "what was old is new again." Just as ideas in child psychology shifted in the 1960s from a focus on behavior to cognitive stages, we are currently seeing a shift away from stages of development toward an emphasis on the interplay between children and the world around them. Specifically, the book offers practical insights into how children can be helped to cope with their changing worlds. These insights emerged in the 1930s, a time of social and economic upheaval much like today. This collection of original papers by former students and colleagues of William E. Blatz, the renowned psychologist and pediatrician known as the "Dr. Spock of Canada," makes a vital contribution by bringing forward and examining his work in the context of contemporary ideas about human development, parenting, and education. The collection forms a prologue to an included guide written by Blatz and colleagues, The Expanding World of the Child. The previously unpublished work articulates a comprehensive functional approach to parenting and childhood education. The unique format of this book will make it useful for courses in parenting, childhood education as well scholarship in child psychology, personality theory, and socialization.